Analisis Firm Value dengan Pemoderasi Corporate Social Responsibility - Pancawati Hardiningsih; Sartika Wulandari; Ceacilia Srimindarti; Rachmawati Meita Oktaviani (Universitas Wahid Hasyim, 2019)
Increasing firm value is a good perception of the company. Maintaining a good reputation can facilitate the addition of capital and increase sales due to public trust. The company's reputation can be maintained through corporate social responsibility (CSR) programs. This study examines the effect of solvency (DER) and company profitability (ROA) on the value of the company with CSR as a moderator. The population of this research is garment and textile companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample used purposive sampling technique, so that it was obtained by 57 observations. The data analysis technique uses a multiple linear regression model of moderation with the based on interaction. Hypothesis test results show that ROA and CSR have a significant positive effect on firm value. While the DER variable does not affect the value of the company. CSR is proven to strengthen ROA towards company value. Keywords: Corporate Value, CSR, Profitability, Solvability.